PROCESS GENRE APPROACH IN TEACHING WRITING NARRATIVE TEXT: ITS IMPLEMENTATION, BENEFITS AND OBSTACLES (A Qualitative Research at a Senior High School in Cianjur) - Elis Homsini Maolida; Pauziah Aisah Al Azhar (Universitas Suryakancana, 2019)
Nowadays, teachers should be more creative and innovative in teaching.In the real condition, students still have difficulties in writing class. To improve students’ writing ability in writing various genres of text, the teacher should choose an innovative strategy. Process genre is one of the approaches commonly used in teaching writing. This research aims to find outthe useof Process Genre Approach in teaching the narrative text as well asthe benefitsand obstacles of using Process Genre Approach in teaching narrative text. This research applied qualitative research. The data of this research were collected from three instruments:classroom observation, questionnaire, and interview. This research was carried out in a senior high school in Cianjurby involving twenty-three students of ten-grade and an English teacher.The first finding shows that in applying process genre approach in teaching writing of narrative text, there were six steps conducted by the teacher following Badger and White (2000) steps: preparation, modeling, planning, join constructing, independent constructing, and revising and editing. The second finding showsthat there were some benefits of using Process Genre Approach in teaching writing narrative text. Teacher’s interview reveals that the benefits of using process genre approach in teaching writing narrative text were the students can write a text step by step and the students not only can write a text but they can learn about a genre of text in detail. In addition, students questionnaire discloses several benefits of using process genre approach in teaching writing narrative text such as the students are easier to write a text and the students can make a text in detail. The last finding shows there were two obstacles, the first was students’low grammar mastery and the second was students low vocabulary mastery.